Agricultural Land Carrying Capacity and Its Implications for Local Food Security in Patilanggio District, Pohuwato Regency, Gorontalo Province - Fitria S. Bagu; Yunnita Rahim; Rahmiyati Modjo; Irma Abdulrahman (International Journal of Technology and Education Research, 2026)
Agricultural land carrying capacity is an important indicator for assessing the capacity of a region to provide space for food production, meet the needs of its population, and maintain the sustainability of land resources. Patilanggio Subdistrict, Pohuwato Regency, Gorontalo Province, has considerable agricultural potential in both food-crop and horticultural sectors. However, it also faces a range of challenges, including population growth, land-use change, increasing food demand, and environmental risks such as flooding and drought. This study aims to analyze agricultural land carrying capacity and its implications for local food security in Patilanggio Subdistrict. The study employed a descriptive quantitative method with a spatial approach. The analysis was conducted by calculating the land carrying capacity index, comparing land availability or agricultural production with population needs, and interpreting the results spatially using a Geographic Information System (GIS). The findings indicate that Patilanggio Subdistrict has relatively favorable spatial land carrying capacity due to its substantial land area and relatively low population density. Nevertheless, the sustainability of food-supporting capacity still requires strengthening through increased land productivity, protection of productive agricultural land, control of agricultural land conversion, development of agricultural infrastructure, and optimization of local commodities. This study confirms that land carrying capacity is a strategic component in supporting local food security and sustainable agricultural development at the subdistrict level.